Altered cerebral blood flow patterns in ankylosing spondylitis: A three-dimensional pseudo-continuous arterial spin labeling study - Fang, Jin; Hua, Kelei; Chen, Feng; Wan, Zhifang; Yin, Yi; Liu, Ping; Wang, Tianyue; Jiang, Guihua (Frontiers in Neuroscience, 2022)
Objective This study aimed to detect the cerebral blood flow (CBF) values changes in patients with ankylosing spondylitis (AS) and to evaluate the correlation between the CBF values and the specific clinical characteristics. Materials and methods Forty-eight patients with AS (43 male and 5 female) and 42 healthy controls (HCs) (38 male and 4 female) were recruited. Three-dimensional pseudo-continuous arterial spin labeling (3D-pCASL) was performed on a 3.0T magnetic resonance imaging (MRI). CBF values were obtained on the Philips post-processing workstation based on arterial spin labeling (ASL) data. The two-sample t-test was used to compare CBF differences. The correlation between CBF values and specific clinical characteristics of AS was evaluated. Results The AS group showed increased CBF values in the right precentral gyrus, the left inferior frontal gyrus, and the left temporal pole compared with HCs the AS group also showed decreased CBF values in the left precuneus and the left superior occipital gyrus compared with HCs. There were no significant correlations between the CBF values and the clinical characteristics including total back pain (TBP), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). Conclusion Patients with AS displayed CBF changes compared with HCs using 3D-PCASL. These results may enhance our understanding of the neural substrates of AS and provide evidence of AS-related neurological impairment.